Immunity to acute virus infections with advanced age - Nikolich-Žugich, Janko (Curr Opin Virol, 2020)
New infections in general, and new viral infections amongst them, represent a serious challenge to an older organism. This review discusses the age-related alterations in responsiveness to infection from the standpoint of virus:host relationship and the host physiological whole-organism and specific immune response to the virus. Changes with age in the innate and adaptive immune system homeostasis and function are reviewed briefly. This is followed by a review of specific alterations and defects in the response of older organisms (chiefly mice and humans) to acute (particularly emerging and re-emerging) viral infections, with a very brief summary of the response to latent persistent infections. Finally, we provide a brief summary of the perspectives for possible interventions to enhance antiviral immunity.